Em busca de uma agenda temática: o Brasil no Conselho de Direitos Humanos da ONU - Spagnuolo Filho, Antônio Sérgio (2012)
With the election of Mr. Luiz Inácio Lula da Silva as president in 2002, Brazil began to pursue a more proactive international policy. In this context, Brazil has asserted itself on various issues at the United Nations Human Rights Council, an organ that is increasingly important to the global human rights debate. Brazil has also shown its willingness to act as a mediator at the council. The objective of this study is to review Brazilian diplomacy at the body, analyze the country's positions there, and compare them to Brazil's overall foreign policy strategy. In doing so, the study will evaluate the coherence between Brazil's rhetoric and practice in the human rights arena